2017
DOI: 10.1007/s10661-017-6071-7
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation of S-metolachlor in plant and soil and effect on enzymatic activities

Abstract: The present study aimed at evaluating the dissipation of S-metolachlor (S-MET) at three doses in maize growing on diverse physico-chemical properties of soil. The effect of herbicide on dehydrogenase (DHA) and acid phosphatase (ACP) activity was estimated. A modified QuEChERS method using LC-MS/MS has been developed. The limit of quantification (0.001 mg kg−1) and detection (0.0005 mg kg−1) were very low for soil and maize samples. The mean recoveries and RSDs for the six spiked levels (0.001–0.5 mg kg−1) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 46 publications
(47 reference statements)
4
10
0
Order By: Relevance
“…Our results confirm that the herbicide or its metabolites may stimulate the activity of microorganisms in the first period, while the activity of DHA decreases with dissipation of the active substance [ 22 ].…”
Section: Resultssupporting
confidence: 80%
“…Our results confirm that the herbicide or its metabolites may stimulate the activity of microorganisms in the first period, while the activity of DHA decreases with dissipation of the active substance [ 22 ].…”
Section: Resultssupporting
confidence: 80%
“…The response of enzymes to changes in soil is a consequence of combination of many biotic and abiotic factors such as the type of fertilization and/or contamination, as well as the type of soil and its physicochemical properties (i.e., pH, organic matter content, humidity, nutrient status), experiment condition (laboratory or field scale) or type of enzyme. When sewage sludge is being used, its origin, treatment technique and contaminant level are important factors influencing soil quality [28,50,52]. In the study conducted by Alvarenga et al [53] no effect of sewage sludge application on Dha activity was demonstrated, which partly confirms our results.…”
Section: Effect Of Sewage Sludge and Glyphosate Application On Soil M...supporting
confidence: 87%
“…The moisture content of cocoa husk is about 14% (w/w) (Daud et al, 2013), this may have facilitated the hydrolysis of endosulfan in pod tissues to form the diol metabolite. Besides, the presence of some endogenous biological enzymes such as lignin peroxidases and pectin methyl esterase (Falade et al, 2016, Kameshwar andQin 2018) may have enhanced the rapid degradation of endosulfan observed on day 0 in pods (Wolejko et al, 2017). These other metabolites were not determined; endosulfan sulfate is reported to be the major metabolite of endosulfan -which also is an intermediary metabolite to the formation of other metabolites in plants and animals via the endosulfan diol route.…”
Section: Theobroma Cacao Vegetationmentioning
confidence: 99%